The Revival of the Past: Privatizing Cultural Practices in the Festival Era - Prasetyo Hery (De Gruyter, 2021)
The issue of indigenous community revivalism is crucial related to identity problems and cultural practices in sustainable development. Capital accumulation through cultural commercialization becomes a means to create a cultural creative sector based on tourism. The case of Osing communities in Banyuwangi, East Java, explained and highlighted the cultural practices of indigenous identity to a political-economic agenda. The research used a discursive analysis method with the findings of several issues. First, there were discrepancies between the indigenous and village institutions over the vision of village development. Second, the emergent forms of elite domination in an indigenous village. Third, the economic profit which is introduced by the market system did not align with the constructed narratives of indigenous people as generous and selfless. Fourth, the revival of cultural tourism is followed by an improvement in the infrastructure as a development indicator. And fifth, the government did not effectively represent the will of the indigenous community. Those emerged the contradiction between maintaining and innovating the tradition as a challenge in cultural tourism projects. The conditions were examined as a politics of culture which is formulated by the state. Hence, cultural practices of indigenous community turned into festivals; notwithstanding, indigenous sustainability is still uncertain.